Netrin-1 expression and targeting in multiple myeloma. Issue 2 (28th January 2022) - Fahed, David; Chettab, AbdelKamel; Mathe, Doriane; Denis, Morgane; Traverse-Glehen, Alexandra; Karlin, Lionel; Perrial, Emeline; Dumontet, Charles
Abstract: Deleted in colorectal cancer (DCC) and uncoordinated-5 (UNC5) receptors, play a key role in tumor progression of several solid tumors by inducing apoptosis when unbound to their ligand netrin-1. Netrin 1 is currently being evaluated as a therapeutic target. These receptors, known as dependence receptors, and their ligands, have not yet been extensively explored in hematological malignancies. Here, we performed a screening of various human myeloma cell lines and bone marrow samples from multiple myeloma patients for netrin-1 and its receptors to determine the expression of netrin 1 and its receptors in multiple myeloma as well as to assess the potential anti-myeloma activity of a novel anti-netrin-1 treatment (NP137). Our results showed heterogeneous expression of netrin-1 and its receptors DCC and UNC5H2(B) in six human myeloma lines. Additionally, immunohistochemistry and flow cytometry showed expression of these molecules in a majority of myeloma patient samples. In vitro NP137 did not induce apoptosis of myeloma cell lines yet enhanced the cytotoxicity of bortezomib and dexamethasone. In vivo, NP137 treatment of SCID mice with established RPMI8226 myeloma tumors led to a reduction of tumor size compared to controls. Ex vivo, NP137 lowered the plasma cells percentage in bone marrow aspirates in a fraction of the patient samples analyzed. These results suggest that netrin signaling could constitute a novel therapeutic target in multiple myeloma.